Network Development for Non-state Health Providers : African Christian Health Associations - Dimmock, Frank; Olivier, Jill; Wodon, Quentin (Taylor and Francis, 2017)
Substantial effort has been put into forming and strengthening national networks of non-state, non-profit health providers in lower- to middle-income contexts. Christian health associations (national umbrella networks of faith-inspired health providers) were first established in the 1950s, and are currently present in an estimated 23 of the 54 countries in Africa. The establishment of CHAs was equally encouraged by faith-based health providers, governments, and external stakeholders. CHAs look different in each context, but perform similar roles: networking diverse institutions and facilities together into a loose system; and establishing a more cohesive sector to simplify and strengthen advocacy and engagement with the government.